The role of molecular chaperones in clathrin mediated vesicular trafficking - Sousa, Rui; Lafer, Eileen M. (Frontiers in Molecular Biosciences, 2015)
The discovery that the 70 kD ‘uncoating ATPase’, which removes clathrin coats from vesicles after endocytosis, is the constitutively expressed Hsc70 chaperone was a surprise. Subsequent work, however, revealed that uncoating is an archetypal Hsp70 reaction: the cochaperone auxilin, which contains a clathrin binding domain and an Hsc70 binding J domain, recruits Hsc70*ATP to the coat and, concomitant with ATP hydrolysis, transfers it to a hydrophobic Hsc70-binding element found on a flexible tail at the C-terminus of the clathrin heavy-chain. Release of clathrin in association with Hsc70*ADP follows, and the subsequent, persistent association of clathrin with Hsc70 is important to prevent aberrant clathrin polymerization. Thus, the two canonical functions of Hsp70—dissociation of existing protein complexes or aggregates, and binding to a protein to inhibit its inappropriate aggregation—are recapitulated in uncoating. Association of clathrin with Hsc70 in vivo is regulated by Hsp110, an Hsp70 NEF that is itself a member of the Hsp70 family. How Hsp110 activity is itself regulated to make Hsc70-free clathrin available for endocytosis is unclear, though at synapses it’s possible that the influx of calcium that accompanies depolarization activates the Ca++/calmodulin dependent calcineurin phosphatase which then dephosphorylates and activates Hsp110 to stimulate ADP/ATP exchange and release clathrin from Hsc70*ADP:clathrin complexes.